Understand your market to attract adult learners. Issue 11 (August 2016) - Hope, Joan
Abstract : When officials at colleges and universities observe declining enrollment in the traditional student population, they often decide to seek out adult students or launch online programs, said Lori Pendleton, director of admissions at Charter Oak State College in Connecticut.